Hubungan pengetahuan dan tindakan vaksinasi COVID-19 di Kecamatan Martapura Timur - Abdurrahman Sidiq sidiq; Esty Restiana Rusida; Eny Hastuti (Universitas Islam Indonesia, 2023)
Background: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the infectious disease causes Coronavirus Disease 2019 (COVID-19). The risk of transmission of COVID-19 in the community is increasing. Therefore, it is necessary to carry out educational interventions related to the application of health procedures and vaccination measures. Vaccination activities are expected to inhibit the spread of and prevent the COVID-19 virus. Objective: This study aimed to determine the relationship between knowledge and COVID-19 vaccination behavior in East Martapura Regency.Method: This study was non-experimental analytical descriptive research using a cross-sectional approach in the East Martapura Regency. The questionnaires were given to 397 respondents. A chi-square test was used to analyze the correlation between the study variables.Results: Most respondents (66.5%) showed average knowledge about the COVID-19 vaccination. More than fifty percent (66.6%) of respondents had inappropriate behavior towards the COVID-19 vaccination. There was a relationship between knowledge and behavior regarding COVID-19 vaccination (p < 0.001).Conclusion: There was a relationship between knowledge and COVID-19 vaccination behavior in East Martapura Regency.